1996
DOI: 10.1302/0301-620x.78b4.0780562
|View full text |Cite
|
Sign up to set email alerts
|

Medial Ankle Pain After Lateral Ligament Rupture

Abstract: A fter a severe ankle sprain the incidence of residual complaints, particularly on the medial side of the joint, is high. We studied a consecutive series of 30 patients who had operative repair of acute ruptures of lateral ligaments. During operation, arthroscopy revealed a fresh injury to the articular cartilage in 20 ankles, in 19 at the tip and/or anterior distal part of the medial malleolus as well as on the opposite medial facet of the talus. In six patients, a loose piece of articular cartilage was found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
139
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 206 publications
(145 citation statements)
references
References 17 publications
2
139
0
4
Order By: Relevance
“…56 Later, van Dijk et al reported 4% fresh talar dome lesions and 67% fresh chondral lesions of any kind in 30 patients who had operative repair of acute ruptures of lateral ligaments. 422 More recently, an even higher incidence was reported, namely 41% of 86 patients with anterior talofibular ligament disruptions and 71% of 92 patients with distal fibular fractures. 376 However, the majority of these reported lesions were located at the cartilage covering the anterior aspect of the medial malleolus and the opposite medial talar facet or the anteromedial rim of the tibial plafond.…”
Section: Epidemiologymentioning
confidence: 96%
See 3 more Smart Citations
“…56 Later, van Dijk et al reported 4% fresh talar dome lesions and 67% fresh chondral lesions of any kind in 30 patients who had operative repair of acute ruptures of lateral ligaments. 422 More recently, an even higher incidence was reported, namely 41% of 86 patients with anterior talofibular ligament disruptions and 71% of 92 patients with distal fibular fractures. 376 However, the majority of these reported lesions were located at the cartilage covering the anterior aspect of the medial malleolus and the opposite medial talar facet or the anteromedial rim of the tibial plafond.…”
Section: Epidemiologymentioning
confidence: 96%
“…49,135,439 Ankle sprains cause intra-articular pressure impact and have a prominent role in the development of traumatic OCDs ( Figure 1). 230,422 The trauma causing the lesion can be a single event or a series of less intense (micro) traumas, which may remain unrecognized in some cases. 63,344 Lateral lesions usually are shallow and oval and caused by a shear mechanism.…”
Section: Etiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Recurrent ankle sprains may alter the biomechanics at the ankle joint which can potentially lead to cartilage degeneration over time [9][10][11][12][13]. Up to 93% of patients with ankle instability have associated intra-articular pathology [14][15][16]. Varus instability of the ankle shifts the contact pressure medially and can lead to osteochondral lesions of the ankle particularly in the central medial talar region [17].…”
Section: Introductionmentioning
confidence: 99%